Circular RNA FNDC3B Protects Oral Squamous Cell Carcinoma Cells From Ferroptosis and Contributes to the Malignant Progression by Regulating miR-520d-5p/SLC7A11 Axis - Jie Yang; Xing-Hua Cao; Ke-Feng Luan; Yun-Dong Huang (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) is a common head and neck malignancy with increasing mortality and high recurrence. Ferroptosis is an emerging programed cell death and plays an essential role in tumorigenesis. Circular RNAs (circRNAs) have been reported as a type of critical regulators in OSCC development. In this study, we identified the function of circular RNA FNDC3B (circFNDC3B) in regulating ferroptosis during the malignant progression of OSCC. Our data demonstrated that the silencing of circFNDC3B by shRNA inhibited GPX4 and SLC7A11 expression and enhanced ROS, iron, and Fe2+ levels in OSCC cells. CircFNDC3B knockdown reinforced erastin-induced inhibitory effect on OSCC cells. The depletion of circFNDC3B repressed cell proliferation and enhanced cell apoptosis of OSCC cells. Mechanically, circFNDC3B was able to increase SLC7A11 by targeting miR-520d-5p. The overexpression of SLC7A11 reversed circFNDC3B depletion or miR-520d-5p-induced ferroptosis phenotypes of OSCC cells. Moreover, tumorgenicity assays in nude mice showed that the depletion of circFNDC3B repressed OSCC cell growth in vivo. Taken together, we concluded that circFNDC3B attenuated ferroptosis of OSCC cells and contributed to OSCC progression by regulating the miR-520d-5p/SLC7A11 axis. CircFNDC3B, miR-520d-5p, and SLC7A11 may serve as potential therapeutic targets of OSCC.